Waiting for Elijah time and encounter in a Bosnian landscape - HaǆiMuhamedović, Safet (New York Oxford Berghahn Books, 2018)
"Waiting for Elijah is an intimate portrait of time-reckoning, syncretism and proximity in one of the world's most polarized landscapes, the Bosnian Field of Gacko. Centred on the shared harvest feast of Elijah's Day, the once eagerly awaited pinnacle of the annual cycle, the book shows how the fractured postwar landscape beckoned the return of communal life that entails such waiting. This seemingly paradoxical situation - waiting to wait - becomes a starting point for a broader discussion on the complexity of time set between cosmology, nationalism and embodied memories of proximity."--
Intro -- Contents -- List of Figures and Tables -- Preface -- Acknowledgements -- Introduction -- Part I. Time and Its Discontents -- Chapter 1. Schizochronotopia, or Elijah's Pitfall -- Chapter 2. Time and Home -- Chapter 3. Time and In-Other -- Chapter 4. Time and Epic Residues -- Part II. The Many Faces of Elijah -- Prelude: A River of Many Names -- Chapter 5. The Georgics: An Extended Poetry of the Land -- Conclusion. Waiting for Elijah -- Bibliography -- Index
Keywords: Landscapes -- Bosnia and Herzegovina -- Religious aspects; Landscapes -- Social aspects -- Bosnia and Herzegovina; Elijah the Prophet's Day -- Bosnia and Herzegovina; Gacko (Bosnia and Herzegovina : Opština) -- Historical geography